Visual compatibility of drainage networks of the river basin jordão extracted from the mdes srtm e aster using simplification and smoothing operators - Tolentino, Franciele Marques [UNESP]; Silva, Claudionor Ribeiro; de Paula Santil, Fernando Luiz (Universidade Federal do Paraná, 2018)
The cartographic generalization aims at adapting the cartographic features and their geographic relations according to the scale of representation of the cartographic product. With the advent of computers, operators allow us to observe this geometric and semantic adaptation of this set of features according to the function and purpose established for this product. With the purpose of visually analyzing the cartographic generalization of linear features extracted from the Digital Elevation Model (MDE), from the application of the simplification and smoothing operators, became the focus of this work. In this case, POINT-REMOVE algorithms for simplification and PAEK were used to smooth drainage networks extracted from MDE ASTER and MDE SRTM, respectively, with 30 and 90 meters of spatial resolution. These operators are available in the ARCGis 10.1 software and the study area was the Jordan River basin (MG). There was control of the positional quality of the topographic map generated in digital media and of the MDEs and the visual comparison occurred with the overlap of these products. For this visual analysis, it was based on the principles of photointerpretation, a model of cartographic communication and the results point out a greater similarity between the linear stretches with the topographic map of this basin, independently of the MDE. On the other hand, spatial resolution and topography interfere with the extraction of this drainage network.
Compatibilidade visual das redes de drenagens da bacia hidrográfica do rio jordão (mg) extraídas dos mdes srtm e aster usando operadores de simplificação e suavização
Keywords: Cartographic generalization; Linear features; Photointerpretation